EMPLOYEE SATISFACTION, ENGAGEMENT AND FINANCIAL PERFORMANCE IN STOCK BROKERAGE COMPANIES - Mo, Nguyen Thi; Binh, Nguyen Thanh; Nhung, Le Thi; Hung, Pham Huy; Cu, Hoang Manh; Linh, Nguyen Thuy; Hai, Tran Van (LPPM Universitas Jambi, 2024)
In the context of human resources in the securities industry being depleted after the Covid-19 pandemic, with strong fluctuations and many risks, maintaining and improving the quality of human resources to meet the, an urgent new development stage for the sustainable development of securities companies. Recent studies around the world to meet the needs of workers mostly focus on fields such as banking, manufacturing, etc. The results show that leadership style or salary has a direct impact on meeting the needs of workers. However, the securities industry with young human resources in developing countries like Vietnam has its own differences. The goal of the study is to clarify the relationship between satisfaction, engagement and financial performance in securities companies in Vietnam after the Covid-19 pandemic. Sample data was collected online by the authors from 225 employees working at securities companies in Vietnam, in the period from September 2023 to December 2023. Using quantitative research on the PLS-SEM linear structural model on SPSS 20 and AMOS 20 software, the results show that securities employees are not really satisfied with their current job, identifying 2 factors. Factors that have a strong influence on the financial performance of securities companies include: (1) Training and advancement and (2) Working environment. This is consistent with the characteristics of securities human resources in Vietnam. The study adds to the understanding of meeting employee needs through training and improving the work environment, which in turn will improve a company's financial performance.